Ligophorus uruguayense sp. nov. (Monogenea, Ancyrocephalidae), a gill parasite from Mugil platanus (Mugiliformes, Mugilidae) in Uruguay - Siquier, G.F. (2009)
The present study describes a new species, Ligophorus uruguayense, parasitizing the gills of Mugil platanus Günther, 1880 from the coast of Uruguay. It differs from all other species of the genus mainly in the shape of the ventral bar, the thick process at the distal end of the inner root of ventral anchors, the J-shaped penis accessory piece and the vaginal tube showing transverse annulations at its distal end, the host species, and geographical distribution. This is the first description of a species of Ligophorus from a mullet in the South Atlantic Ocean. © 2009 Versita Warsaw and Springer-Verlag Berlin Heidelberg.